Group Coordination Proceedings under the Recast EIR in practice - Pepels, Sid (European Insolvency and Restructuring Journal, 2023)
On 27 June 2022, at the passing of the European Insolvency Regulation (recast)’s lustrum, the European Commission will have to present a report on the application of the so-called group coordination proceeding. This proceeding was introduced into EU insolvency law in order to tackle coordinative problems that arise in cross-border insolvencies relating to groups of companies, for those cases were mere ad hoc communication and cooperation amongst insolvency practitioners is insufficient. Nearing this five-year anniversary, it has become apparent that the group coordination proceeding has not been applied in practice to date. The author sets out to review the added value of the group coordination proceedings, to analyze which reasons could exist for its lack of practical application and to evaluate which changes, if any, would improve the group coordination proceeding’s usefulness as a group restructuring tool.